FUS P525L mutation causing amyotrophic lateral sclerosis and movement disorders. Issue 6 (19th April 2020) - Zhou, Binbin; Wang, Huan; Cai, Yu; Wen, Han; Wang, Lulu; Zhu, Min; Chen, Yunqing; Yu, Yanyan; Lu, Xi; Zhou, Meihong; Fang, Pu; Li, Xiaobing; et al.
Abstract: Background: Mutations in the fused in sarcoma (FUS) gene have been associated with amyotrophic lateral sclerosis (ALS), frontotemporal lobar degeneration, and essential tremor. Among the FUS mutations, p.P525L as a hot spot variant has been reported in more than 20 patients with ALS. Apart from the typical ALS phenotype, patients with p.P525L mutation exhibit some atypical symptoms. However, movement disorders related to p.P525L mutation have not been emphasized currently. Methods: Two unrelated patients with ALS were evaluated through a set of clinical and laboratory tests. The genetic screening was performed through next‐generation sequencing. Muscle biopsies were performed on the 2 patients. Muscle samples were stained according to standard histological and immunohistochemical procedures. Results: The first patient presented with juvenile‐onset neurogenic weakness and wasting and simultaneously had dropped head, ophthalmoplegia, tremor, involuntary movements, and cognitive impairments. The second patient showed a typical ALS phenotype and prominent adventitious movements. Genetic screening disclosed de novo p.P525L FUS mutation in the 2 patients by family cosegregation analysis. Muscle biopsy showed neurogenic patterns and numerous lipid droplets aggregating in the fibers. Conclusion: Apart from the typical ALS phenotype, patients with p.P525L mutation in the FUS gene can present with great clinical heterogeneity including multiple movement disorders. Numerous lipid droplets in muscle fibers indicate that skeletal muscle is likely an important therapeutic target for ALS. Abstract : Besides the typical ALS phenotype, patients with p.P525L mutation in the FUS gene can present with great clinical heterogeneity including multiple movement disorders. Numerous lipid droplets in muscle fibers indicate that skeletal muscle is likely an important therapeutic target for ALS.